Respuesta :
Answer: x= 5-√10 / 3
x= 5 + √10/ 3
Step-by-step explanation:
-(-10) +- √(-10)^2 -4 x 3 x 5 / 2x 3
x= 10 +- √100-60 / 6
x=10 +- √ 40
simplify to x = 10 +- 2√10 / 6
simplify both equations now
divide both equations by 2 which gives the answer.
Answer:
[tex]x=\frac{5+ \sqrt{10}}{3}\,,\,\frac{5- \sqrt{10}}{3}[/tex]
Step-by-step explanation:
Let [tex]ax^2+bx+c=0[/tex] be a quadratic equation where a , b , c are coefficients and a ≠ 0.
Using quadratic formula, roots are given by [tex]x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
On comparing equation [tex]3x^2-10x+5=0[/tex] with equation [tex]ax^2+bx+c=0[/tex] , we get [tex]a=3\,,\,b=-10\,,\,c=5[/tex]
First , we will find [tex]b^2-4ac[/tex] :
[tex](-10)^2-4(3)(5)=100-60=40[/tex]
So, [tex]\sqrt{b^2-4ac}=\sqrt{40}=2\sqrt{10}[/tex]
Now, using quadratic formula, we will find roots of the equation .
[tex]\begin{align*}\displaystyle x &=\frac{10\pm 2\sqrt{10}}{6}\\\displaystyle &=\frac{5\pm \sqrt{10}}{3}\\\displaystyle &=\frac{5+ \sqrt{10}}{3}\,,\,\frac{5- \sqrt{10}}{3}\\ \end{align*}[/tex]